2003
DOI: 10.1167/iovs.02-0892
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Protection against Corneal Damage by Free Radicals during Phacoemulsification

Abstract: The addition of ascorbic acid to the irrigation solution significantly reduced the amount of endothelial cell loss during phacoemulsification by approximately 70%. This is thought to be due to the free-radical-scavenging properties of ascorbic acid. Further studies are warranted to find the optimal concentrations and combinations of free radical scavengers to be used in phacoemulsification irrigation solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 36 publications
4
62
0
5
Order By: Relevance
“…Reports of corneal endothelial damage secondary to the use of ultrasound during phacoemulsification have been attributed to the release of free radicals due to cavitation. [131][132][133][134] However, the aqueous humor is rich in antioxidants, including ascorbic acid, and the lens has a coating of glutathione, another effective antioxidant. These endogenous antioxidants provide some endothelial protection.…”
mentioning
confidence: 99%
“…Reports of corneal endothelial damage secondary to the use of ultrasound during phacoemulsification have been attributed to the release of free radicals due to cavitation. [131][132][133][134] However, the aqueous humor is rich in antioxidants, including ascorbic acid, and the lens has a coating of glutathione, another effective antioxidant. These endogenous antioxidants provide some endothelial protection.…”
mentioning
confidence: 99%
“…5 In addition, there are some recent studies that have shown that the phacoemulsification-associated endothelial injury may be caused by free radicals. [6][7][8][9] Based on these findings, it seems likely that the corneal endothelium can be damaged by free radicals during phacoemulsification because free radical species, hydroxyl radicals in particular, are highly reactive and can cause lethal injuries to cells. 10 The purpose of this study was to investigate the effects of free radicals on the corneal endothelium with special emphasis on histologic and immunohistochemical analyses after performing ultrasound oscillation in the anterior chambers of rabbit eyes.…”
mentioning
confidence: 99%
“…A szabadgyök-képződés az egyik legfontosabb, a szür-kehályog-műtét során kialakuló endothelsejt-károsodás-hoz vezető folyamat [11][12][13][14][15].…”
Section: Eredeti Közleményunclassified